Persepsi Petani Padi Sawah Terhadap Teknologi Tanam Tebar Benih Langsung (TABELA) Dan Tanam Pindah (TAPIN) Di Kabupaten Kubu Raya: Persepsi, Petani Padi Sawah, Tabela, Tapin - Mahrani Fiansyah; Dewi Kurniati; Adi Suyatno (JURNAL AGRICA, 2023)
The rice commodity has always been the main farming business in an area because this commodity is a producer of rice whose demand is always high for people's daily food needs. The need for a relatively high workforce and a long time in cultivating rice farming is a problem faced by farmers. The purpose of this study was to analyze the differences between the transplanting system (Tapin) and the direct seed planting system (Tabela) in terms of total productivity, production costs, number of workers and profits and find out how farmers perceive the transplanting system (Tapin) and the direct seed planting (Tabela). The method used is quantitative descriptive and uses the Paried Sample t-Test method and data is analyzed using SPSS. This study used 70 samples which were taken by purposive sampling because the respondents had already implemented both cropping systems. The results of this study show that the average profit of lowland rice farming in Kubu District, Kubu Raya Regency with the tabela system is Rp.14,945,744 while the tapin system is Rp.10,100,145 per planting season. Based on the different tests, there are significant differences between productivity, production costs, labor and profits. The perception of lowland rice farmers in Kubu District, Kubu Raya Regency, on the direct seed planting system was included in the high category with a total score of 58.8 and a percentage of 62.86%, while the transplanting system was included in the medium category with a total score of 40. 62 and with a percentage of 65.71%. This shows that the perception of lowland rice farmers in the direct seed planting system is better than the transplanting system.